The assessment of structural concretes during construction phases. Issue 3 (8th July 2014) - Uva, Giuseppina; Porco, Francesco; Fiore, Andrea; Mezzina, Mauro
Abstract : Purpose: – The purpose of this paper is to collect the numerical elaboration of resistances measured on cubes made during the concrete casting and on cores extracted after the completion of the structure, for the concrete used in the construction of the "Esaro" Dam facilities (Cosenza, Italy). In addition to the statistical treatment of the sample, aimed at assessing the analytical congruence with the homogeneous classes provided in the design, the influence of compaction degree on in place strength value was qualitatively evaluated. Design/methodology/approach: – The reliability of the concrete during the construction phases was evaluated by two analytical control types according to Italian and European technical rules: "production controls" based on statistical processing of resistance values; "laying controls" that serve to assess the compaction degree with a statistical approach. Findings: – Results highlighted in the assessing of compliance checks of the mixture, the fundamental relation between statistical approach and concrete laying control. They become important when is necessary to quantify, especially in the case of great infrastructure, the gap between "potential" and "structural" concrete. Originality/value: – The advantage obtained by controlling the compaction degree in the construction phase is unquestionable. Specifically, it might allow a reduction of the drilling cores, and so minor structural damage, especially for relatively recent structures favouring extensive non-destructive tests.